CG4928 Is Vital for Renal Function in Fruit Flies and Membrane Potential in Cells: A First In-Depth Characterization of the Putative Solute Carrier UNC93A - Ceder, Mikaela M.; Aggarwal, Tanya; Hosseini, Kimia; Maturi, Varun; Patil, Sourabh; Perland, Emelie; Williams, Michael J.; Fredriksson, Robert (Frontiers in Cell and Developmental Biology, 2020)
The number of not fully characterized transporter proteins is immense.; Hhere we used D. melanogaster and human cell cultures lines to study perform a first in-depth characterization of CG4928, an orthologue to the human UNC93A, a protein of which little is known. Solute cCarriers regulate and maintain biochemical pathways important for cellsthe body, and malfunctioning transport is associated with multiple diseases. Based on phylogenetic analysis, CG4928 is closely related to human UNC93A and has a secondary and a tertiary protein structure and folding, a protein with a similar protein folding asto Major Facilitator superfamily transporters. Ubiquitous knockdown of CG4928 causes flies to have a reduced secretion rate from the Malpighian tubules; and altered potassium content in the body and Malpighian tubules, homologous to the renal system; , resultand resultsing in the development of edema. The edema could be rescued using Amiloride, a common diuretic and by maintaining the flies on ion-free diets. CG4928 overexpressing cells did not facilitate transport of sugars and amino acids, however, proximity ligation assay revealed that CG4928 co-localize with TASK1 channels. Overexpressing of CG4928 resulted in induced apoptosis and cytotoxicity, which could be restored when cells were kept in high sodium media. Furthermore, the basal membrane potential was observed to be disrupted. Taken together, the results indicate that CG4928 is of importance for generating the cellular membrane potential by unknown manner. However, we speculate that it most likely act as a regulator or transporter of potassium flows over the membrane.